Analisis Faktor-Faktor yang Memengaruhi Struktur Modal - Rita Njo; Jonnardi (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
The purpose of this study is to obtain empirical evidence on the effect of profitability, asset structure, and liquidity on capital structure for consumer goods industry companies listed in Indonesian Stock Exchange during year 2016-2020. Sample was selected using simple random sampling method amounted to 36 samples. Data processed using random effect model and multiple linear regression analysis with helped by EViews 10. The results of this study shows that profitability has no significant influence towards capital structure, asset structure has positive and significant influence towards capital structure, while liquidity has negative and significant influence towards capital structure.